2013
DOI: 10.1371/journal.pone.0067242
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Receptor Blocker Attenuates Intrarenal Renin-Angiotensin-System and Podocyte Injury in Rats with Myocardial Infarction

Abstract: The mechanisms and mediators underlying common renal impairment after myocardial infarction (MI) are still poorly understood. The present study aimed to test the hypothesis that angiotensin II type 1 receptor blockers (ARBs) provides renoprotective effects after MI by preventing augmented intrarenal renin-angiotensin-system (RAS)-induced podocyte injury. Sprague–Dawley rats that underwent ligation of their coronary arteries were treated with losartan (20 mg/kg/d) or vehicle for 3 or 9 weeks. Renal function, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 31 publications
3
14
0
Order By: Relevance
“…There was no significant interaction with total and LDL-cholesterol ( p = 0.71 and p = 0.80 in the BLSA sample, respectively; and p = 0.56 and p = 0.22 in the MAGIC one), glycated hemoglobin ( p = 0.14 in the BLSA sample, which included diabetic subjects), and hsCRP ( p = 0.65 in the MAGIC sample, in which CRP values were available). The IGF-1 system is also influenced by the RAAS [34,35]. Consistent with this, a significant interaction was found between IGF-1 and aldosterone in the MAGIC population ( p = 0.003).…”
Section: Resultssupporting
confidence: 59%
“…There was no significant interaction with total and LDL-cholesterol ( p = 0.71 and p = 0.80 in the BLSA sample, respectively; and p = 0.56 and p = 0.22 in the MAGIC one), glycated hemoglobin ( p = 0.14 in the BLSA sample, which included diabetic subjects), and hsCRP ( p = 0.65 in the MAGIC sample, in which CRP values were available). The IGF-1 system is also influenced by the RAAS [34,35]. Consistent with this, a significant interaction was found between IGF-1 and aldosterone in the MAGIC population ( p = 0.003).…”
Section: Resultssupporting
confidence: 59%
“…PE is a prominent risk factor for ESKD; 19 in women with three or more pregnancies, those with one PE pregnancy have a relative ESKD risk of 6.3 (95%CI: 4.1-9.9), while those with two PE pregnancies have a relative ESKD risk of 15.5 (95%CI: 7.8-30.8) compared with women with no PE pregnancies. 19 In an animal model, angiotensin receptor blocker (ARB) had a renoprotective effect via podocyte protection, 20 and was indeed shown to confer significant renal benefits in patients with type 2 diabetes and nephropathy, resulting in reduced proteinuria. 21 Although contraindicated in pregnancy, 22 use of ARB can be considered for renoprotection in post-partum women after PE pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study [3] and another report [4] have revealed the presence of injury to the podocytes, key parenchymal cells within the glomerular, in rat models with left ventricular dysfunction. Our prior research suggests that undue activation of the local renin angiotensin system (RAS) within the kidneys is an important marker for the pathogenesis of podocyte injury post-MI [3].…”
Section: Introductionmentioning
confidence: 91%
“…Experimental MI was induced in rats by left coronary artery ligation as described in our previous work [3,6,7]. Briefly, male Sprague-Dawley rats weighing about 300 g were anesthetized with sodium pentobarbital (intraperitoneal, 30 mg/kg), intubated, and then ventilated with a rodent respirator.…”
Section: Experimental MI and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation